2001
DOI: 10.1378/chest.119.5.1576
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Exercise ECG in Patients With Diabetes and Chest Pain

Abstract: Objective: The purpose of this study was to determine the characteristics of exercise treadmill testing in diabetic patients presenting with chest pain. Background: The diagnosis of coronary artery disease (CAD) in diabetic patients is confounded by different manifestations of coronary disease than are seen in the general population. Because of the association of diabetes with accelerated CAD, it is critical to assess the diagnostic utility of the standard exercise test in diabetic patients with chest pain. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…24,25 Elhendy et al 24 evaluated the importance of exercise echocardiography for risk stratification of such patients with known or suspected ischemic heart disease. A total of 563 patients underwent symptom-limited treadmill testing that involved 1 of the 3 following protocols: Bruce, Naughton, or modified Bruce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Elhendy et al 24 evaluated the importance of exercise echocardiography for risk stratification of such patients with known or suspected ischemic heart disease. A total of 563 patients underwent symptom-limited treadmill testing that involved 1 of the 3 following protocols: Bruce, Naughton, or modified Bruce.…”
Section: Discussionmentioning
confidence: 99%
“…Their data indicated that patients with diabetes mellitus who had an abnormal stress echocardiogram were at greater risk of death or nonfatal myocardial infarction than those with a normal stress echocardiogram. 24 Lee and colleagues 25 sought to determine the characteristics of exercise treadmill testing in patients with diabetes who had angina. They conducted a retrospective analysis of exercise test results in 1282 men who had undergone coronary angioplasty and were without prior myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…[411][412][413][414][415][416] ECG stress testing has an approximate 50% sensitivity and 80% specificity. 401 The positive predictive value for detecting CAD using coronary angiography as the gold standard ranges between 60% and 94% and was higher in men than women.…”
Section: Electrocardiographic Stress Testing For Silent Myocardial Ismentioning
confidence: 99%
“…Given the differences in presentation of CAD within the diabetic population and particularly the higher incidence of silent myocardial ischemia, various groups have attempted to evaluate whether the exercise ECG has similar accuracy in a diabetic population. Lee et al 30 (Table 1) retrospectively evaluated 190 diabetic patients among 1282 male veterans presenting with chest pain who underwent an exercise ECG test and coronary angiography within a 4-month period. With standard ECG criteria used to define a positive test, 1 38% of diabetic patients had an abnormal exercise test, whereas 69% had CAD as defined by angiography.…”
Section: Diagnostic Valuementioning
confidence: 99%